Adenovirus vector vaccination induces expansion of memory CD4 T cells with a mucosal homing phenotype that are readily susceptible to HIV-1 - Benlahrech, Adel (National Academy of Sciences, 2009)
In the recently halted HIV type 1 (HIV-1) vaccine STEP trial, individuals that were seropositive for adenovirus serotype 5 (Ad5) showed increased rates of HIV-1 infection on vaccination with an Ad5 vaccine. We propose that this was due to activation and expansion of Ad5-specific mucosal-homing memory CD4 T cells. To test this hypothesis, Ad5 and Ad11 antibody titers were measured in 20 healthy volunteers. Dendritic cells (DCs) from these individuals were pulsed with replication defective Ad5 or Ad11 and co-cultured with autologous lymphocytes. Cytokine profiles, proliferative capacity, mucosal migration potential, and susceptibility to HIV infection of the adenovirus-stimulated memory CD4 T cells were measured. Stimulation of T cells from healthy Ad5-seropositive but Ad11-seronegative individuals with Ad5, or serologically distinct Ad11 vectors induced preferential expansion of adenovirus memory CD4 T cells expressing α(4)β(7) integrins and CCR9, indicating a mucosal-homing phenotype. CD4 T-cell proliferation and IFN-γ production in response to Ad stimulation correlated with Ad5 antibody titers. However, Ad5 serostatus did not correlate with total cytokine production upon challenge with Ad5 or Ad11. Expanded Ad5 and Ad11 memory CD4 T cells showed an increase in CCR5 expression and higher susceptibility to infection by R5 tropic HIV-1. This suggests that adenoviral-based vaccination against HIV-1 in individuals with preexisting immunity against Ad5 results in preferential expansion of HIV-susceptible activated CD4 T cells that home to mucosal tissues, increases the number of virus targets, and leads to a higher susceptibility to HIV acquisition.